2017
DOI: 10.2471/blt.16.179291
|View full text |Cite
|
Sign up to set email alerts
|

Quality of routine essential care during childbirth: clinical observations of uncomplicated births in Uttar Pradesh, India

Abstract: ObjectiveTo evaluate the quality of essential care during normal labour and childbirth in maternity facilities in Uttar Pradesh, India.MethodsBetween 26 May and 8 July 2015, we used clinical observations to assess care provision for 275 mother–neonate pairs at 26 hospitals. Data on 42 items of care were collected, summarized into 17 clinical practices and three aggregate scores and then weighted to obtain population-based estimates. We examined unadjusted differences in quality between the public and private f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…Numerous studies done in India and comparative studies in Southeast Asia indicate that perception of quality of care is important in deciding where to deliver. [ 16 17 18 19 20 21 22 ] Our findings are consistent with a similar study in Nepal that suggests women perceived private facilities to be higher on the scale of quality for better privacy, improved infrastructure, and more cleanliness. [ 17 ] In our study, mothers perceived that quality of care provided in private sector compared to public sector was better.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Numerous studies done in India and comparative studies in Southeast Asia indicate that perception of quality of care is important in deciding where to deliver. [ 16 17 18 19 20 21 22 ] Our findings are consistent with a similar study in Nepal that suggests women perceived private facilities to be higher on the scale of quality for better privacy, improved infrastructure, and more cleanliness. [ 17 ] In our study, mothers perceived that quality of care provided in private sector compared to public sector was better.…”
Section: Discussionsupporting
confidence: 89%
“…[ 23 24 25 ] The comparison of public and private sector in Uttar Pradesh shows that quality of care observed during the births was better in private facilities compared to public sector. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Door-to-door observation of the entire journey of a woman’s experience of delivery care allowed identification of critical gap areas specific to each of the five stages. Few other studies have similar in-depth documentation [ 22 , 27 , 46 48 ]. These studies were conducted in similar settings—Ethiopia; Nigeria; UP and MP in India and most of them used direct observations of intrapartum care provided during labour and childbirth except one in Nigeria that employs a different qualitative approach to capture the experiences of providers and women.…”
Section: Discussionmentioning
confidence: 94%
“…According to a hospital-based cross-sectional study conducted in Netherland the active third stage management was being adequately performed in only close to half of all vaginal deliveries [ 54 ]. Other gaps include inappropriate maternal and newborn infection management, not providing immediate skin to skin contact and no assessment of newborn’s health [ 22 , 46 , 55 ]. Gaps in patient safety included providers not performing hand hygiene before wearing sterile gloves, instruments not being sterilized; and improper disposal of sharps.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have identified gaps between recommended and actual practices [2]. Essential routine monitoring and assessment during labour as well as key practices are not sufficiently conducted, compounded by inappropriate infrastructures and supplies [3][4][5]. Mistreatment and abusive actions, including unnecessary interventions, are also common in health facility deliveries [4,6].…”
Section: Introductionmentioning
confidence: 99%